ANALISIS PENERAPAN PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KREATIVITAS SISWA DI SEKOLAH DASAR: Jurnal Skripsi - Adinda Rahma Yundira; Nurul Febrianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education serves not merely as a channel for transferring academic content but also as a space where learners can develop a variety of essential abilities. Among these abilities, creativity is considered a central competence that must be nurtured from the early years of elementary education. Yet, in practice, numerous elementary schools continue to depend on outdated instructional methods, which often restrict opportunities for students to think imaginatively. To overcome this challenge, it is necessary to apply teaching strategies that actively stimulate creative growth, and one promising alternative is the project-based learning model. The objectives of this study are twofold: first, to examine whether project-based learning has a positive effect on enhancing creativity among elementary students, and second, to explore in detail how this instructional model can be practically implemented in classroom contexts. Adopting a qualitative methodology in the form of library research, this study reviews relevant literature and finds that project-based learning strengthens creativity through six systematic stages accompanied by project-oriented activities. These findings suggest that project-based learning provides a valuable contribution as an innovative instructional approach that can be integrated into elementary education to foster students’ creative capacities.